2019
DOI: 10.1002/ett.3791
|View full text |Cite
|
Sign up to set email alerts
|

Detection of clone scammers in Android markets using IoT‐based edge computing

Abstract: Pirated application developers find an alternate way to publish pirated versions of the same Android mobile applications (apps) on different Android markets.Therefore, a centralized, automated scrutiny system among multiple app stores is inevitable to prevent publishing pirated or cloned version of these Android applications. In this paper, we proposed an Android clone detection system for Internet of things (IoT) (Droid-IoT) devices. First, the proposed system receives an original Android application package … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For this reason, distinguishing repackaged or fake applications and analyze the behaviors of variants is also an essential task. From the collected primary studies, six studies apply deep learning techniques to detect variants [16,77,108,109,163,164]. By unpacking a software package and then repackaging it after a purposeful modification of original codes, a fake application with malicious intention is created to misguide mobile users to install it in application markets.…”
Section: Results Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, distinguishing repackaged or fake applications and analyze the behaviors of variants is also an essential task. From the collected primary studies, six studies apply deep learning techniques to detect variants [16,77,108,109,163,164]. By unpacking a software package and then repackaging it after a purposeful modification of original codes, a fake application with malicious intention is created to misguide mobile users to install it in application markets.…”
Section: Results Analysismentioning
confidence: 99%
“…By unpacking a software package and then repackaging it after a purposeful modification of original codes, a fake application with malicious intention is created to misguide mobile users to install it in application markets. In order to locate mobile counterfeit applications in application markets, Ullah et al [163] and Karunanayake et al [77] propose DL-based Fake app detectors to prevent the publishing of fake apps in app stores. Except that, there are two primary studies on the detection of variants of malware families [108,164].…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have also used an artificial bee colony attack detection which helps to recognize the eavesdropper. In Reference 41, the authors suggested a clone detection system for the IoT devices for Android. They have used a deep learning model to predict clones in Android applications.…”
Section: Related Workmentioning
confidence: 99%